Libraries, Archives and Museums as Democratic Spaces in a Digital Age - Audunson, Ragnar; Andresen, Herbjørn; Fagerlid, Cicilie; Henningsen, Erik; Hobohm, Hans-Christoph; Jochumsen, Henrik; Larsen, Håkon; Vold, Tonje (Current Topics in Library and Information Practice, 2020)
Libraries, archives and museums have traditionally been a part of the public sphere's infrastructure. They have been so by providing public access to culture and knowledge, by being agents for enlightenment and by being public meeting places in their communities. Digitization and globalization poses new challenges in relation to upholding a sustainable public sphere. Can libraries, archives and museums contribute in meeting these challenges?